2019
DOI: 10.1158/1078-0432.ccr-18-2407
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Checkpoint Inhibitor Combinations and Administration Timing Can Be Measured by Granzyme B PET Imaging

Abstract: Purpose: The lack of a timely and reliable measure of response to cancer immunotherapy has confounded understanding of mechanisms of resistance and subsequent therapeutic advancement. We hypothesized that PET imaging of granzyme B using a targeted peptide, GZP, could be utilized for early response assessment across many checkpoint inhibitor combinations, and that GZP uptake could be compared between therapeutic regimens and dosing schedules as an early biomarker of relative efficacy. Experimental Design: Two m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 25 publications
(33 reference statements)
4
86
0
Order By: Relevance
“…Another interesting target of immune Cancers 2020, 12, 371 8 of 23 response could be the protease granzyme B (GZP), which is secreted by cytotoxic CD8+ and has a key role for immune-induced apoptosis [43]. In preclinical tumor models, a highly specific peptide PET imaging agent for GZP was predictive of the response to immune-checkpoint inhibitors, with high signal tumors responding to therapy and with 93% sensitivity and 94% negative predictive value [44]. Clinical studies have yet to be done.…”
Section: Immunoimagingmentioning
confidence: 99%
“…Another interesting target of immune Cancers 2020, 12, 371 8 of 23 response could be the protease granzyme B (GZP), which is secreted by cytotoxic CD8+ and has a key role for immune-induced apoptosis [43]. In preclinical tumor models, a highly specific peptide PET imaging agent for GZP was predictive of the response to immune-checkpoint inhibitors, with high signal tumors responding to therapy and with 93% sensitivity and 94% negative predictive value [44]. Clinical studies have yet to be done.…”
Section: Immunoimagingmentioning
confidence: 99%
“…Despite the tremendous potential of antibody‐based tracers, they have slow blood clearance that leads to long waiting time (eg, several days) between imaging scan and tracer injection, which prevents the clinical transformation of the molecular imaging. In this setting, a number of protein‐ or peptide‐based radiotracers have been fabricated to compensate the pitfalls of the antibody‐based probes . For example, Trotte et al developed a 18 F‐labeled affibody ligand that can effectively detect PD‐L1 expression in xenograft tumors by PET imaging, with preferable specificity, fast blood clearance, and low normal tissue uptake except nephridia .…”
Section: Imaging Biomarkers For Immune Checkpoint Therapymentioning
confidence: 99%
“…In this setting, a number of protein-or peptide-based radiotracers have been fabricated to compensate the pitfalls of the antibody-based probes. [84][85][86][87][88][89][90][91] For example, Trotte et al developed a 18 F-labeled affibody ligand that can effectively detect PD-L1 expression in xenograft tumors by PET imaging, with preferable specificity, fast blood clearance, and low normal tissue uptake except nephridia. 85 Larimer et al demonstrated that granzyme B PET imaging might serve as an effective biomarker for predicting responses to immunotherapy in human tumor xenograft models.…”
Section: Anti-pd-l1mentioning
confidence: 99%
See 1 more Smart Citation
“…To predict response at the earliest stages, biomarkers of immune cell activation are requisite. Upon successful immunotherapy, immune cells are activated and then home to the tumor tissue where they can (25,26), have shown promising results both for response monitoring and assessment of therapeutic strength. However, these secreted biomarkers pose challenges for imaging including half-life and dilution.…”
Section: Introductionmentioning
confidence: 99%